Facile preparation of attapulgite‐based aerogels with excellent flame retardancy and better thermal insulation properties. Issue 32 (22nd April 2019) - Liang, Weidong; Wang, Ran; Wang, Chengjun; Jia, Juan; Sun, Hanxue; Zhang, Jianli; Yang, Yueyue; Zhu, Zhaoqi; Li, An
ABSTRACT: A novel and environmentally friendly attapulgite‐based aerogel with a three‐dimensional fibrillary network structure was prepared by incorporation of nanometer‐sized natural clay crystals, in this case attapulgite (ATP), into degradable poly(vinyl alcohol) (PVA), cotton cellulose nanowhisker, and melamine using only a simple blending method and subsequently a freeze‐drying process. The ATP‐based aerogel exhibits an abundant porosity with an average mesopore size of 8.0 nm in diameter. Compared to fragile and rigid inorganic aerogels, the as‐prepared aerogel shows good flexibility and mechanical strength with a compressive strength of 9.65 × 10 4 Pa and 10.19 × 10 4 Pa at 20% and 40% of compressive strain, respectively. The limiting oxygen index (LOI) and vertical flame tests show that the resulting aerogel possesses excellent flame retardancy, with an LOI of 59.5%. Microcalorimetry test results show that the total heat release of the aerogel is as low as 5.1 KJ/g. Also, the sample shows a better thermal insulation property, with a thermal conductivity of about 0.045 W m −1 K −1 in air. Taking advantage of a simple and environmentally friendly fabrication, abundant natural clay resources, easy scalability, nearly no pollution emission in the process, and cost‐efficient production, the ATP‐based aerogel has great potential as ideal flame retardant and thermal insulation materials for many applications such as modern building construction or energy‐efficient coatings. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47849. Abstract :